2012
DOI: 10.4161/epi.20830
|View full text |Cite
|
Sign up to set email alerts
|

Global DNA methylation levels in white blood cell DNA from sisters discordant for breast cancer from the New York site of the Breast Cancer Family Registry

Abstract: Lower global DNA methylation is associated with genomic instability and it is one of the epigenetic mechanisms relevant to carcinogenesis. Emerging evidence for several cancers suggests that lower overall levels of global DNA methylation in blood are associated with different cancer types, although less is known about breast cancer. We examined global DNA methylation levels using a sibling design in 273 sisters affected with breast cancer and 335 unaffected sisters from the New York site of the Breast Cancer F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 43 publications
1
38
2
Order By: Relevance
“…The genome of breast cancer cells is typically characterized by global hypo-methylation, and this assumption is supported by results of a meta-analysis study, in which breast cancer risk has been found to be significantly higher for women with the lowest GDM compared with the counterpart group with the highest GDM levels [169]. Global hypomethylation in white blood cells has also been reported to be related with increased risk of breast cancer [170,171]. Global DNA hypo-methylation can promote breast cancer development via several signaling pathways, including triggering genomic instability, activation of oncogenes, and inducing metastasis formations [172,173].…”
Section: Epigenetic and Breast Cancermentioning
confidence: 77%
“…The genome of breast cancer cells is typically characterized by global hypo-methylation, and this assumption is supported by results of a meta-analysis study, in which breast cancer risk has been found to be significantly higher for women with the lowest GDM compared with the counterpart group with the highest GDM levels [169]. Global hypomethylation in white blood cells has also been reported to be related with increased risk of breast cancer [170,171]. Global DNA hypo-methylation can promote breast cancer development via several signaling pathways, including triggering genomic instability, activation of oncogenes, and inducing metastasis formations [172,173].…”
Section: Epigenetic and Breast Cancermentioning
confidence: 77%
“…DNA methylation is one type of epigenetic change that has been associated with cancer, and recent studies have shown that global changes in DNA methylation in peripheral tissue such as blood are correlated with increased risk of different cancers, including breast. [6][7][8][9][10] Our group also found that global DNA methylation levels, measured by the methyl acceptance assay, and levels in the repeat Sat2 were lower in women with breast cancer when compared with their unaffected sisters. 7,8 Therefore, it has been hypothesized that lower global DNA methylation in peripheral tissue may be an indicator of an individual's susceptibility to breast cancer.…”
Section: Introductionmentioning
confidence: 84%
“…[6][7][8]19 However, lower levels of LINE-1 have been associated with increased risk of gastric, head and neck, bladder, liver, and testicular cancer. 17,[20][21][22][23] Increased breast cancer risk has been found to be related to lower DNA methylation of the repetitive element Sat2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, some researchers have suggested that methylation analysis of repetitive elements such as LINE1, sat2 and Alu in WBC may be a surrogate for genomic hypomethylation. Based on this approach, some studies have shown that these repetitive elements in the leukocytes of healthy women with a family history of breast cancer are hypomethylated [16,46] as well as breast cancer patients compared to controls [8,21,47].…”
Section: Evidences Based On Whole Genome Approachmentioning
confidence: 99%